La frontière : contrainte ou ressource pour l’individu ? Le « pari romantique » des pionniers de la Société des missions évangéliques de Paris, de « l’humanisation » à « l’humanitarisation » des Sotho - Laurence Espinosa (Les Cahiers de Framespa)
The paper suggests thinking about the imaginary, imagined and true border, from the case of protestant missionaries from XIXth century and Sotho of Southern Africa. It is about the border as a fluctuating object, tangible object of the tensions between reality and its images. The adventure of the pioneers envisaged as romantic, the politic role and the figure of paramount chief Moshoeshoe, and the symbolic dimension of named, converted persons, were favourite approaches to describe these variations as tangles, overtaking, bypass, or diversions. Beyond this first approach, our thought wants to propose a heuristic process from any corpus or field, through possibilities given by the questioning from the original context and its different and successive receptions.